Gifted and talented students' career aspirations and influences: A systematic review of the literature - Miller, Kathleen; Cummings, Greta (My University, 2009)
The nursing shortage of registered nurses in Canada is expected to worsen, making recruitment a concern for nursing organizations. Also, many reports have outlined the need for improved leadership in nursing. Therefore, the study purpose was to describe the findings of a systematic review of studies examining the career influences and aspirations of gifted high school students and to make recommendations for further research. Results indicate gifted students choose careers that fit their personal self-concept and their perceptions of traits needed to succeed in a profession. Family members, particularly mothers, had the greatest influence on career decision making and these students were more likely to indicate a desire for a profession with high prestige, high levels of education and higher pay. These students were not likely to indicate nursing as a career choice. Efforts to improve the image of nursing with this group of students are needed.
Keywords: career aspirations; career influences; systematic review; gifted high school students; social talent